Brain–computer interfaces and 3d design manufacturing in a postdigital scenario. Issue 1 (31st December 2022) - Ranzo, Patrizia; Scarpitti, Chiara
Abstract: The paper describes the results of seven-year experimental research between manufacturing processes of product design and the BCI - Brain–Computer Interfaces field, afferent to neuroscience. From analyzing a postdigital scenario and the emergence of a series of case studies, the essay proposes theoretical-applicative research that develops new cooperation between BCI and object-oriented 3d printing technologies. From a humanistic perspective, the paper identifies the postdigital scenario as a conjunction plane between the constant bio-technological acceleration and digital culture. In the interaction of BCI with the Internet of Things, the contribution illustrates the meaning of the primary brain frequencies and some wearable devices able to detect them. The essay then describes the rise in the last decade of a series of design experiences on the borderline between design and neuroscience, highlighting how these technological hybridizations can lead to the singularization of objects. The final part carries out its path of technological innovation into practice through the experimentation of two processes: Alpha and Flows . The most operative part of the process investigates the interaction between different brain waves and software, the BCI's connection with the subjects, and the 3d printing of the results. Both experimental phases implement hybrid manufacturing processes, involving citizens in a process of scientific awareness through direct interaction with the artifacts created. By showing the expressive possibilities and touchpoints between neuroscience and design, the contribution tries to be a tangible manifestation of a design culture that integrates different scientific knowledge and skills. The conclusions place the adoption of BCIs within a conscious digital design aimed at a double outcome: on the one hand, bringing citizens closer to neuroscience issues, and on the other, activating transdisciplinary processes towards a hybrid production.